A constraint based formalisation for distributed cooperative sensor resource allocation. (1st October 2010) - Matsui, Toshihiro; Matsuo, Hiroshi
Distributed sensor resource allocation problem is an important research area of multi-agent systems. In this paper, we focus on distributed resource allocation problem for distributed sensor networks. Formalisations which represent distributed sensor networks as distributed constraint networks have been proposed in previous researches. Applying distributed optimisation algorithm is a useful approach to understand the problems and to design the cooperative protocols. On the other hand, a distributed cooperative observation system using agency model has been developed. The agency model has been applied to practical distributed cooperative sensor network. We observe several models based on constraint network and another model based on concept of agency. Then we show a constraint based formalisation that are similar to resource allocation problem of agency model. The goal of the formalisation is to integrate DCOP and agency model. An experiment is made to evaluate the formalisation.